المغامرة الجديدة في رواية النجدي لطالب الرفاعي: The new adventure in Najdi's novel by Talib Al-Rifai - Al-Rubaie, Ishraq Same (SIBAWAYH Arabic Language and Education, 2021)
يناقش البحث رواية النجدي لطالب الرفاعي مقترحا لها تسمية "المغامرة الروائية الجديدة". وهو يتابعها في علاقتها بمصطلح المغامرة الروائية القديمة التي تنهض على سرد ارتحالي، هو الجامع بين النوعين السرديين، مع إحداث تطوير عليهما، يتمثل في جوانب الاختيار، وغياب الاستكشاف. وكلاهما يفسحان مجالا لأهم مزايا الشكل في هذا النوع من السرد، المتمثلة بخصوصية الموضوع، وطبيعة المنظور، وما يترتب عليهما من دلالة، ومن سمة سردية، تجعل من هذا النوع من السرد مغامرة كتابة، شأنه شأن أنواع التخييل المختلفة، من ذاتي وتاريخيThe research discusses Al-Najdi's novel by Talib Al-Rifai, suggesting it be called "the new narrative adventure." He follows it in its relation to the term of the old fictional adventure that revolves around a nomadic narrative, which combines the two types of narrative, with the development of them, represented in aspects of choice and the absence of exploration. And both of them give room for the most important features of the form in this type of narration, represented by the specificity of the subject, the nature of the perspective, and the significance they entail, and the narrative characteristic that makes this type of narration a writing adventure, just like the different types of fiction, both subjective and historical.Keywords: Adventure, novel, traditional, new, narrative.